2015
DOI: 10.1099/jmm.0.000088
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of vancomycin-resistant Enterococcus faecium strains isolated from carriage and clinical samples in a tertiary hospital, Turkey

Abstract: This study aimed to determine the presence of vancomycin resistance (vanA and vanB) and virulence genes (esp, asa1, gelE, ace, hyl, cylA, cpd and ebpA) in vancomycin-resistant Enterococcus faecium (VREfm) strains and to analyse the clonal relationships among the strains. E. faecium strains were identified from rectal and clinical specimens by biochemical tests and the API-20 Strep kit. Susceptibility testing was performed using disc-diffusion and broth-dilution methods. PFGE was used for molecular typing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
5
19
0
2
Order By: Relevance
“…In our study, the presence of the esp gene was more common in infecting (17, 35 %) as compared with colonizing (eight, 6 %) or water isolates (nine, 13 %). The percentage of esp-positive infecting clinical isolates was comparable with that reported in other studies, where 41 % and 30 % of enterococci carried this gene (Gozalan et al, 2015;Upadhyaya et al, 2011). Even higher rates of esp carriage have been reported, ranging from 52 % to 77 % (Comerlato et al, 2013;Ruiz-Garbajosa et al, 2006;Tsikrikonis et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, the presence of the esp gene was more common in infecting (17, 35 %) as compared with colonizing (eight, 6 %) or water isolates (nine, 13 %). The percentage of esp-positive infecting clinical isolates was comparable with that reported in other studies, where 41 % and 30 % of enterococci carried this gene (Gozalan et al, 2015;Upadhyaya et al, 2011). Even higher rates of esp carriage have been reported, ranging from 52 % to 77 % (Comerlato et al, 2013;Ruiz-Garbajosa et al, 2006;Tsikrikonis et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Even though the percentage of biofilm production from infecting isolates (54 %) is comparable to that reported in previous studies (38-93 %) (Comerlato et al, 2013;Duprè et al, 2003;Gozalan et al, 2015;Ira et al, 2013;Tsikrikonis et al, 2012), biofilm synthesis from colonizing isolates (13 %) was low (Johansson & Rasmussen, 2013;Tsikrikonis et al, 2012). Furthermore, Tsikrikonis et al (2012) found that 70 % of colonizing isolates were biofilm producers, whereas, in the study of Johansson & Rasmussen (2013), biofilm synthesis was more common in normal flora isolates as compared with those recovered from infective endocarditis.…”
Section: Discussionsupporting
confidence: 60%
“…Libisch et al [18] reported that the vanA gene was the dominant gene among invasive isolates in Serbia. Similar results were obtained for hospitalized patients in Turkey [27]. As per Werner et al [28], the vanA and vanB resistance genotypes are by far the most prevalent in Europe.…”
Section: Discussionsupporting
confidence: 85%
“…VanC confers only lowlevel resistance to vancomycin [24,25]. Compared to other phenotypes, the VanA is the most common in European countries [26,27]. Our results confirmed this fact: 100% of VREfm strains belong toVanA phenotype.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, Gözalan et al reported that all 55 VREfm strains carried the vanA gene. 13 In other studies, from Turkey, the rate of vanA carriage has been determined to be 84-100%. [14][15][16] The vanA type resistance is dominant in the United States and Europe, whereas vanB type resistance is more frequent in Australia and Southeast Asia.…”
Section: Discussionmentioning
confidence: 97%